Counselling: The Current Opium of the People? - Carton, Tony (Scientific Research, 2015)
Western religion’s propensity to stultify holiness and the sacred is eclipsed in the profession of counselling. With its fundamentalist enthralment with the individual self, this poster-girl of liberalism, through its central modus-operandi, language has achieved a privileged rhetoric thereby relegating itself to the dustbin of history certainly in Western society. It is less a “sigh of the oppressed soul” (Marx, 1978) as the empowerment of an opportunistic harlotry that energises the profession in a neoliberal marketplace with discourses of social justice routinely cheapened and ideologically hijacked. The author designates a genealogy of this ascendant plummet learnt through retrospective insight. Counsellors have not only unconditionally accepted tablets of stone around truths but also binaries of truths. Interrogating several sacred cows in the profession including the concept of burnout, the should/need dichotomy and the parallel process he apprehends a trajectory chronicling nodal points and concluding that many undertakings within counselling serve increasingly to perpetuate a political-non-political conflation with marketplace morality idealised as liberalism morphs seamlessly into neoliberalism. What descends from a neoliberal paradise are reconfigurations of dichotomies not” of our choosing” (Marx, 1978) but of our own choice. Willingly with the anesthetising of any coherent Judeo-Christian impulses we opt for the sanctity of a vacuous Starbuck spirituality as liberalism or religion in its “degutted” version (Eagleton, 2009: p. 41) enacts the comfort of the afflicted but never the affliction of the comfortable.
Keywords: Neoliberalism; Foucault; Addiction; Resilience; Religion